Waste Bank Management Assistance in Realizing Green Village in Cikalong Village, Cikalong Wetan District, West Bandung Regency - Awan Gunawan; Saepulloh; Rahman Wahid (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This article discusses waste bank management assistance as an effort to realise a Green Village in Cikalong Village, Cikalong Wetan District, West Bandung Regency. The purpose of this activity is to increase community awareness about effective and sustainable waste management, and promote environmentally friendly practices. The methods used include training, socialisation, and direct assistance to the community in waste bank management. The results of this assistance showed an increase in community participation in sorting organic and inorganic waste, as well as a reduction in the volume of waste disposed of in the landfill. In addition, the programme succeeded in empowering the community through economic activities from waste processing. In conclusion, waste bank management assistance plays a significant role in supporting the creation of a clean and sustainable environment in Cikalong Village, as well as encouraging active community participation in protecting the environment.